(untitled) (Contemporary Journal of Social Science Review, 2025)
The abusive custodial practices in Pakistan are eroding human rights policies. This article attempts to tackle the myriad forms of such abuses, particularly the role of law and order institutions alongside their exacerbating system. Pakistan, in spite of International human rights treaties and its own constitution, practices custodial torture, illegal imprisonments, and mental abuse of detainees. This research shows the vicious cycle of custodial violence stems from the enforcement of antiquated practices, institutionalized overconfidence with a lack of accountability, and fractured silos lacking oversight. While some headway has been made around the phenomenon due to elite cases or media attention, advocacy from other civil society groups, and multi-stakeholder initiatives which aided public discourse around custodial violence, real reform remains elusive. Furthermore, the article evaluates the social and psychological effect on the victims and the secondary consequences on governance and citizen’s trust towards the state. The state legal system as well as International legal documents impose an immediate necessity for changes on laws or establishment of independent bodies free of political manipulation that could regulate the police autonomously, alongside specialized education for these leaders. It becomes apparent that only a transversal approach affecting the nation’s underlying constructs can enable relevant transformation. Adding insights from countries with better custodial arrangements enhances the relevance of reform proposals.